2022
DOI: 10.1038/s41388-022-02413-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of lncRNA LVBU in regulating urea cycle/polyamine synthesis axis to promote colorectal carcinoma progression

Abstract: Altered expression of Urea Cycle (UC) enzymes occurs in many tumors, resulting a metabolic hallmark termed as UC dysregulation. Polyamines are synthesized from ornithine, and polyamine synthetic genes are elevated in various tumors. However, the underlying deregulations of UC/ polyamine synthesis in cancer remain elusive. Here, we characterized a hypoxia-induced lncRNA LVBU (lncRNA regulation via BCL6/urea cycle) that is highly expressed in colorectal cancer (CRC) and correlates with poor cancer prognosis. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The potential clinical application prospect of circRNA is huge (Liang et al, 2022). CircRNA is often abnormally expressed and expressed in cerebrovascular disease and high tissue speci city (Meng et al, 2022). Therefore, targeted therapy targeting circRNA may be developed into a new way to treat cerebrovascular disease in the future, and theoretically, it may not cause the harmful side effects to healthy tissues (Miozzo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential clinical application prospect of circRNA is huge (Liang et al, 2022). CircRNA is often abnormally expressed and expressed in cerebrovascular disease and high tissue speci city (Meng et al, 2022). Therefore, targeted therapy targeting circRNA may be developed into a new way to treat cerebrovascular disease in the future, and theoretically, it may not cause the harmful side effects to healthy tissues (Miozzo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent ndings have also con rmed that circRNA has a variety of biological functions, including regulating the chromosome recombination, controlling the gene transcription, pre-transcription mRNA processing, and affecting the protein signal function and localization (Liang et al, 2022). CircRNAs involved in stroke also have a wide range of mechanisms, including DNA inactivation, methylation, transcriptional promotion, activation of other RNA molecules, and so on (Bauer et al, 2022;Meng et al, 2022). Moreover, scientists have found that circRNA can undergo various epigenetic modi cations, including methylation and ubiquitination, and act as ceRNA with some microRNAs (miRNAs) to form a regulatory network (Siegerist et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Luciferase Reporter Assay: Luciferase reporter assay was performed as previously described. [44] Basically, cells seeded in 24-well plates were transfected with indicated amount of pGL3 or pGL3-pEIF3F containing a TCF7L2 transcription factor binding site on EIF3F, pRL-CMV, and pCMV-MYC-TCF7L2 expressing plasmid into HEK293T cells. After 48 h, cells were lysed, and the reporter activity was assayed with the dual luciferase assay system (Promega, #E1960) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia‐induced exosomal miR‐135a‐5p is involved in the development, clinical severity, and prognosis of CRC liver metastases through the pre‐metastatic niche 134 . LncRNA LVBU promotes CRC progression by regulating urea cycle/polyamine synthesis axis 135 . These papers studied the mechanism of CRC metastasis using the PDX model.…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%
“… 134 LncRNA LVBU promotes CRC progression by regulating urea cycle/polyamine synthesis axis. 135 These papers studied the mechanism of CRC metastasis using the PDX model. Overall, PDX models are becoming more common in CRC basic research.…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%